Acute effects of video-game playing versus television viewing on stress markers and food intake in overweight and obese young men: A randomised controlled trial. (1st January 2018) - Siervo, Mario; Gan, Jason; Fewtrell, Mary S.; Cortina-Borja, Mario; Wells, Jonathan C.K.
Abstract: Background: Sedentary or near-sedentary activities are associated with overweight/obesity in epidemiological studies. This has traditionally been attributed to physical activity displacement. A little-explored area is whether behavioural stresses alter sensations of appetite and eating behaviour. We examined whether behaviours conducted seated (television viewing, video gaming) induce different eating patterns, associated with differential levels of stress response. Methods and findings: We conducted a randomized controlled trial in 72 overweight/obese adult males, assigned to three groups (24 per group): (i) non-violent television (control group); (ii) non-violent game (FIFA); (iii) violent game (Call of Duty). Following a standardized breakfast, the 1-h intervention was followed by 25-min rest, with sweet and savoury snacks and drinks available ad libitum . Stress markers (heart rate, blood pressure, visual analogue scale (VAS)) were measured throughout. Heart rate, systolic blood pressure, and stress by VAS were significantly higher ( p  < 0.05) playing video games than watching non-violent television, though the two game groups did not differ. Considered separately, only the violent video game group consumed more energy (Δ = 208.3 kcal, 95%CI 16, 400), sweet foods (Δ = 25.9 g, 95%CI 9.9, 41.9) and saturated fat (Δ = 4.36 g, 95%CI 0.76, 7.96) than controls. Conclusion: Playing video games in overweight/obese adult males is associated with an acute stress response relative to watching non-violent television, associated with greater subsequent food intake. These findings highlight the need to focus on the metabolic effects, as well as the energy costs, of activities involving sitting in relation to obesity risk.